Penambahan Heat Exchanger Untuk Recovery Steam Pada Venting 2-E-006 Untuk Dijadikan Kondensat - Novelasari, Nita (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
PT. Multi Nitrotama Kimia (MNK) is a leading provider of mining explosives and blasting services in Indonesia, producting nitric acid and ammonium nitrate. In the productiion process, excess steam generated by the wet heat boiler is vented into atmosphere. This study aims to recover the thermal energy from the vented steam by adding a Shell and Tube Heat Exchanger is utilized with a cross-flow configuration, where steam flows through the shell side and cooling water through the tube side. The exchanger is designed with a shell diameter of 406.4 mm (16 inches) and tube outer diameter of 19.05 mm (¾ inch) following IPS (Iron Pipe Size) standards and BWG 16 wall thickness. The unit consists of 90 tubes, each 2 meters long, arranged in a triangular pitch layout to optimize heat transfer area. Tubes are made of stainless steel to ensure corrosion resistance. The effective heat transfer area is calculated to be 27.05 m². The system produces condensate at 99.59°C with a flow rate of 1087.26 kg/h and achieves energy savings up to Rp945,529,832 annually.